Distribution of neuropeptide Y-like immunoreactivity in the brain of Salmo salar and Gambusia affinis - García-Fernández, J.M.; Del Brío, M.A.; Cernuda-Cernuda, R.; Coto, A.; Riera, P. (Murcia : F. Hernández, 1992)
Through the imrnunohistochernical PAP technique, the distribution of irnrnune positive neurons and fibres for an antibody anti-NPY in the encephalon of salrnon fixed in Bouin have been located and studied. NPY-positive neurons are found forming three important nuclei: in the ventrolateral telencephalon; in the tegmentum mesencephali; and in the locus coemleus. Neurons in the optic tecturn, in the thalarnic region and a few in the preoptic recess have also been located. The fibres were found throughout the brain, with the exception of the cerebellurn, presenting a greater density in three regions: in the dorsal telencephalon; in the mesencephalon; and in the visceral lobes in the rhombencephalon. With the airn of proving if this distribution is found in other groups of teleosts, we processed, with the sarne technique, the advanced teleost Gambusia affinis, in order to compare it with the prirnitive teleost Salmo salar. The results show that in both fish this neuropeptide has the same pattem of distribution. The results also suggest that in fish this neuropeptide can be involved in severa1 functions of the central nervous systern, as has been dernonstrated for rnarnmals. The innervation of the visceral lobes and also the presence of NPY-fibres in the posterior hypothalarnus are anatornical supports of the studies which suggest that NPY is related to the control of the food intake.